PENGARUH PEER GROUP TUTORIAL TERHADAP PERILAKU JAJAN SEHAT SISWA KELAS 3 DI SD ISLAM HIDAYATULLAH DENPASAR SELATAN - Laksmi Perdana (Coping: Community of Publishing in Nursing, 2014)
Snacking activity at school time has become a habit for kids on school age. The number of unhealthy snacks around the school area is remained high and snacking behavior become a new health problem. One attempts to influence the healthy snacks behavior through a peer group tutorial. This research aims to prove that peer group tutorial influence the healthy snacks behavior of 3rd grade students in SD Islam Hidayatullah Denpasar Selatan. The study was conducted using pre-experimental research design, namely a one group pre-post test design. Sample obtained using a total sampling technique with the number of samples is 28 persons. This research held for 8 days with the increase of knowledge from sufficient knowledge to be good knowledge, the increase of attitude from good attitude to be very good attitude and the increase of action from sufficient action to be good action. Based on the Wilcoxon test, obtained a significant value of p = 0,000 < ? 0,05. The results of this study indicate that there is significant effect of peer group tutorial on healthy snacks behavior of 3rd grade students in SD Islam Hidayatullah Denpasar Selatan. It is recommended to the health workers to use this method to increase the number of healthy snacks behavior.